Prevalencias de la epilepsia en infantes: revisión sistemática y metaanálisis - Gutama Chilpe, Eliza Gabriela (2025)
Childhood epilepsy is a highly prevalent neurological disorder. A systematic review following PRISMA guidelines and a meta-analysis of proportions were conducted to estimate its global prevalence. The results show high heterogeneity and higher rates in Africa and Asia, with significant cognitive and educational implications.